The “I’m Feeling Lucky Syndrome”: Teacher-Candidates’ Knowledge of Web Searching Strategies - Corinne Laverty; Brenda Reed; Elizabeth Lee (Partnership: The Canadian Journal of Library and Information Practice and Research, 2008)
The need for web literacy has become increasingly important with the exponential growth of learning materials on the web that are freely accessible to educators. Teachers need the skills to locate these tools and also the ability to teach their students web search strategies and evaluation of websites so they can effectively explore the web by themselves. This study examined the web searching strategies of 253 teachers-in-training using both a survey (247 participants) and live screen capture with think aloud audio recording (6 participants). The results present a picture of the strategic, syntactic, and evaluative search abilities of these students that librarians and faculty can use to plan how instruction can target information skill deficits in university student populations.